Peran Mahasiswa KPM UNSIQ dalam Meningkatkan Kualitas Air Sumur Bor Desa Kaliwader Menggunakan Filtrasi Air dengan Sistem Aerator Venturi - Umu Aiman Alhabasiah; Tazkia Aulia Ramadhanty; Shelsabella Qoulan Sadida; Tri Hargiyani; Luluk Alawiyah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Clean water quality is an important factor in supporting public health. In Kaliwader Village, Bener District, Purworejo Regency, drilled well water is used as the main source of clean water, however, based on initial testing, discrepancies were still found in several water quality parameters, particularly turbidity. The Community Service Lecture (KPM) activity of the Al-Qur'an Science University (UNSIQ) aims to improve the quality of drilled well water through the implementation of a water filtration system combined with a venturi aerator and providing education to the community about clean water management. The method used is a descriptive method with an observational approach, including water sampling, laboratory testing at the Regional Health Laboratory UPT, and the implementation of a Malang sand-based filtration unit with venturi aeration. The test results showed that the water turbidity level before treatment reached 8 NTU, exceeding the established quality standards. After the implementation of the filtration system and venturi aerator, the physical quality of the water improved, marked by a decrease in turbidity and an increase in water clarity. Chemical and microbiological parameters were generally within safe limits according to the Regulation of the Minister of Health of the Republic of Indonesia Number 2 of 2023. This activity demonstrated that the application of simple technology by UNSIQ KPM students can play an effective role in improving the quality of drilled well water and supporting the provision of more adequate clean water for the people of Kaliwader Village.